Food insecurity and the role of food assistance programs in supporting diet quality during the COVID-19 pandemic in Massachusetts - Lee, Matthew M.; Poole, Mary Kathryn; Zack, Rachel M.; Fiechtner, Lauren; Rimm, Eric B.; Kenney, Erica L. (Frontiers in Nutrition, 2023)
Background: Economic and supply chain shocks resulting from the COVID-19 pandemic in 2020 led to substantial increases in the numbers of individuals experiencing food-related hardship in the US, with programs aimed at addressing food insecurity like the Supplemental Nutrition Assistance Program (SNAP) and food pantries seeing significant upticks in utilization. While these programs have improved food access overall, the extent to which diet quality changed, and whether they helped mitigate diet quality disruptions, is not well understood. Objective: To evaluate food insecurity, food pantry and/or SNAP participation associations with diet during the COVID-19 pandemic among Massachusetts adults with lower incomes. Methods: We analyzed data from 1,256 individuals with complete data. Current dietary intake was assessed via food frequency questionnaire. Using Bayesian regression models, we examined associations between pandemic food insecurity, perceived disruption in diet, diet quality, and intakes of individual foods among those who completed a survey in 2020. We assessed interactions by pantry and SNAP participation to determine whether participation moderated these relationships. Results: Individuals experiencing food insecurity reported greater disruption in diet during the pandemic and reduced consumption of healthy/unhealthy foods. Pantry participation attenuated associations between food insecurity and lower consumption of unhealthy (from b = -1.13 [95%CI -1.97;0.31] to -0.70 [-2.24;0.84]) and healthy foods (-1.07 [-1.82;0.34] to 0.30 [-1.17;1.74]), whereas SNAP attenuated associations for healthy foods alone (-1.07 [-1.82;0.34] to -0.75 [-1.83;0.32]). Results were robust to choice of prior as well as to alternative modeling specifications. Conclusions: Among adults with lower incomes, those experiencing food insecurity consumed less food, regardless of healthfulness, compared to individuals not experiencing food insecurity. Participation in safety-net programs, including SNAP and pantry participation, buffered this phenomenon. Continued support of SNAP and the food bank network and a focus on access to affordable healthy foods may simultaneously alleviate hunger while improving nutrition security.